Đặc điểm biến dạng thẳng đứng Holocen - Đệ Tứ vùng Tây Bắc Việt Nam - Thắng, Ngô Gia; Bách, Lê Duy; Thủy, Nguyễn Ngọc (Vietnam Journal of Earth Sciences, 2007)
The characteristics of vertical displacement in the Northwest territory of Vietnam in Pliocene-Quaternary stage